Pharmacokinetic/Pharmacodynamic (PK/PD) Simulation for Dosage Optimization of Colistin Against Carbapenem-Resistant Klebsiella pneumoniae and Carbapenem-Resistant Escherichia coli - Kamonchanok Jitaree; Korbtham Sathirakul; Jantana Houngsaitong; Orarik Asuphon; Weerayuth Saelim; Visanu Thamlikitkul; Preecha Montakantikul (MDPI AG, 2019)
The purpose was to explore the optimal dosage regimen of colistin using Monte Carlo simulations, for the treatment of carbapenem-resistant Klebsiella pneumoniae and carbapenem-resistant Escherichia coli based on PK/PD targets in critically ill patients. A total of 116 carbapenem-resistant K. pneumoniae and E. coli were obtained from various clinical specimens at Siriraj Hospital in Bangkok, Thailand. Minimum inhibitory concentrations (MICs) of colistin were determined by broth microdilution method. Monte Carlo simulation was used to calculate the cumulative fraction of response (CFR) for European Medicine Agency (EMA), US-Food and Drug Administration (FDA), Nation et al., Siriraj Hospital and our study regimens. The targeted CFR was 90%. For colistin-susceptible K. pneumoniae, all of the dosage regimens achieved ≥90% CFR in patients with creatinine clearance <80 mL/min except the FDA-approved regimens for patients with creatinine clearance 51−79 and 11−29 mL/min, respectively. While, patients with creatinine clearance ≥80 mL/min, CFR ≥90% was observed in Siriraj Hospital and our study regimen. For colistin-susceptible E. coli, all of the dosage regimens achieved ≥90% CFR regardless of renal function. In contrast, the currently approved regimens achieved CFR target in only 10-50% for colistin-resistant isolates subgroup. These results suggest that currently approved regimens still recommended for colistin-susceptible CRE. For colistin-resistant CRE, alternative approaches such as high dose or combination therapy should be considered.